Serotypes & penicillin susceptibility of Streptococcus pneumoniae isolated from children admitted to a tertiary teaching hospital in Malaysia - Subramaniam, Prasanna; Jabar, Kartini Abdul; Kee, Boon Pin; Chong, Chun Wie; Nathan, Anna Marie; De Bruyne, Jessie Anne; Thavagnanam, Surendran; Chua, Kek Heng; Md Yusof, Mohd Yasim; Teh, Cindy Shuan Ju (Medknow Publications, 2018)
Background & objectives: Streptococcus pneumoniae (pneumococcus) is a highly invasive extracellular pathogen that causes diseases such as pneumonia, otitis media and meningitis. This study was undertaken to determine the serotype diversity and penicillin susceptibility of S. pneumoniae isolated from paediatric patients in a tertiary teaching hospital in Malaysia. Methods: A total of 125 clinical isolates collected from January 2013 to May 2015 were serotyped using seven sequential multiplex polymerase chain reactions. The susceptibility of these isolates to penicillin was also investigated. Results: Serotypes detected among the isolates were serotypes 3, 6A/B, 6C, 11/A/D/F, 15A/F, 19A, 19F, 23A, 23F, 34. Serotypes 19F and 6A/B were the most prevalent serotypes detected. Most of the S. pneumoniae were isolated from nasopharyngeal samples of children below five years of age. Majority of the isolates were penicillin susceptible. Only 5.6 per cent of the isolates were non-susceptible to penicillin, mostly of serotype 19F. Interpretation & conclusions: Our study revealed the distribution of various serotypes in S. pneumoniae isolates obtained from children in a teaching hospital at Kuala Lumpur, Malaysia and decreasing rates of penicillin resistance among them. The shifts in serotypes and susceptibility to penicillin from time to time have been observed. Continuous monitoring and surveillance are pivotal for better infection control and management of pneumococcal infections among children.